Role of Bone Scintigraphy in Modification and Finalization of the Pathological Staging of Carcinoma of Breast - Farhana, Sharmin; Hussain, Raihan; Mutsuddy, Pupree; Ferdous, Jesmin; Begum, Shamim MF (Bangladesh Journal of Nuclear Medicine, 2018)
Objectives: The prognosis and treatment planning of carcinoma depends upon the stage of the disease. The presence of bone metastasis affects a patient’s prognosis and further treatment planning. The purpose of this study was whether bone scintigraphy by detecting skeletal metastasis can help in patient management by modification of initial pathological staging. Patients and Methods: A total of 110 patients of breast carcinoma who were referred for the early bone scintigraphy after the surgical procedure were included in this study. Bone scintigraphy was done 3 hours after 15 m Ci Tc-99m methylelene diphosphonate (MDP) intravenous injection. Images were acquired in Siemens E-cam dual head camera. Chi-Square test was used to analyze the variables Results: Out of the total 110 patients with breast carcinoma referred to the institute after initial pathological staging nearly one third i.e. 31 (28.2%) patients had skeletal metastasis. In this study it was revealed that tumour size and nodal involvement correlated well with metastasis to bone. Skeletal metastasis was significantly (p<0.05) higher in tumour size belonged to >3.0 – ≥5.0 cm and nodal involvement N2–N3(p<0.05). Sixty eught of the patients were in pathological stage II, among them 22.1% of the patients had skeletal metastasis. Pathological stage III was observed in 33 cases, among them 48.5% patients had skeletal metastasis and as thus staging was modified by bone scintigraphy in 22.1% in stage II and 48.5% in stage III. Pathological stage I was in 9 cases among them no metastasis was observed. Conclusion: Bone scintigraphy is a useful imaging modality in staging of breast carcinoma. It is recommended in patients with stage II and above and this can influence the clinical management. Bangladesh J. Nuclear Med. 19(2): 107-110, July 2016